ER-Phagy, ER Homeostasis, and ER Quality Control: Implications for Disease. Issue 8 (August 2021) - Ferro-Novick, Susan; Reggiori, Fulvio; Brodsky, Jeffrey L.
Abstract : Lysosomal degradation of endoplasmic reticulum (ER) fragments by autophagy, termed ER-phagy or reticulophagy, occurs under normal as well as stress conditions. The recent discovery of multiple ER-phagy receptors has stimulated studies on the roles of ER-phagy. We discuss how the ER-phagy receptors and the cellular components that work with these receptors mediate two important functions: ER homeostasis and ER quality control. We highlight that ER-phagy plays an important role in alleviating ER expansion induced by ER stress, and acts as an alternative disposal pathway for misfolded proteins. We suggest that the latter function explains the emerging connection between ER-phagy and disease. Additional ER-phagy-associated functions and important unanswered questions are also discussed. Highlights: The selective degradation of the endoplasmic reticulum (ER), termed ER-phagy or reticulophagy, has multiple physiological functions. Many different types of cell stress can induce ER-phagy, including starvation and misfolded protein accumulation. ER-phagy pathways participate in ER homeostasis and ER quality control. ER-phagy performs functions that are independent of the unfolded protein response (UPR) and ER-associated degradation (ERAD). ER-phagy pathways, that play a role in ER quality control, are cytoprotective.